What We Are When We Are: Kaj smo, ko smo - Cvetka Lipuš, translated by Tom Priestly (Athabasca University Press, 2021)
Working within a postmodern style, this rhythmic and melodious collection of poems originally written in Slovenian by Cvetka Lipuš and translated here by Tom Priestly, blends the real with the surreal, dull urban lives with dreams. Lipuš, known for the lexical beauty of her work, dwells on topics of time and space which she handles in an almost revolving, irreverent manner. Priestly captures the maze-like characteristic of her verse and carefully reconstructs the sonoric beauty of the work in its original language.